Mind the output gap: The new technocratic politics of EU fiscal rules in Italy - Camilla Locatelli (Max Planck Institute for the Study of Societies, 2024)
The sovereign debt crisis triggered a process of reforms in European economic governance that pushed for technocratic handling of budget decisions following standardized procedures, target measures, and indicators for fiscal monitoring. This shift, aimed at producing more stability and less conflict in budget decision-making, transformed fiscal policy, producing a new type of technocratic fiscal politics. These new technocratic instruments impact on national policymaking, yet little is known about the processes and actors behind their constitution. Scholarship on the policy response to the euro area crisis has highlighted the role of national interests but neglected the role of expertise in negotiating highly technical fiscal policies. A key measure in this new technical apparatus, the output gap, has been at the center of a heated contestation between Italian and European institutions over the 2014-2019 period. Taking the case of the Italian output gap, this paper traces the unfolding of the dispute around the methodology for estimating potential output and clearly reveals the new centrality of expertise. The paper argues that rather than producing a less conflictual policy environment and a depoliticizing of fiscal decisions, technocratic fiscal politics has reshaped discussions around budgetary politics. This reshaping extends and transforms actor constel- lations and venues of fiscal decisions, giving a larger role to technocratic experts. – – Die Staatsschuldenkrise hat einen Reformprozess in der wirtschaftspolitischen Steuerung Europas in Gang gesetzt, der auf eine technokratische Handhabung von Budgetentscheidungen nach standardisierten Abläufen, Zielvorgaben und Indikatoren für die Finanzkontrolle abzielt. Die Reformen sollten zu mehr Stabilität und weniger Konflikten in Budgetentscheidungsprozessen führen, stattdessen aber entstand eine neue Art technokratischer Fiskalpolitik. Dieses neue technokratische Instrumentarium hat Auswirkungen auf die nationale Politikgestaltung, wobei wenig über die Prozesse und Akteure bekannt ist, die bei seiner Entstehung eine Rolle gespielt haben. Die Fachliteratur zur politischen Reaktion auf die Eurokrise betont die Rolle nationaler Interessen, vernachlässigt aber die Bedeutung von Expertenwissen bei der Aushandlung hochtechnischer fiskalpolitischer Maßnahmen. Ein zentrales Werkzeug dieses Instrumentariums, die Produktionslücke, war zwischen 2014 und 2019 Gegenstand hitziger Debatten zwischen italienischen und europäischen Institutionen. Am Beispiel der italienischen Produktionslücke zeichnet das Papier die Entwicklung des Streits um die Methoden der Potenzialschätzung nach und hebt die neue zentrale Bedeutung von Expertise hervor. Es wird argumentiert, dass die Technokratisierung der Fiskalpolitik nicht etwa zu einem weniger konfliktreichen Politikumfeld und einer Entpolitisierung von Steuerentscheidungen geführt hat, sondern vielmehr zu einer Neugestaltung haushaltspolitischer Debatten. Diese Neugestaltung verändert und erweitert in der Folge Akteurskonstellationen und Schauplätze fiskalpolitischer Entscheidungen und verleiht technokratischer Expertise eine größere Bedeutung.
hdl:21.11116/0000-000F-FF6F-7
Keywords: 300; European Union; fiscal policy; Italy; output gap; technocracy; Europäische Union; Fiskalpolitik; Italien; Produktionslücke; Technokratie